Airspace restrictions due to conflicts increased global aviation’s carbon dioxide emissions in 2023 - Grégoire Dannet; Nicolas Bellouin; Olivier Boucher (Communications Earth & Environment)
Abstract As air traffic rebounds from its large drop during the Covid-19 crisis, civil aviation needs to continue addressing its climate impact. Knowledge of aircraft trajectories is essential for an accurate assessment of the CO2 (and non-CO2) climate impact of aviation. Here we combine an aircraft trajectory optimization algorithm and a global database of aircraft movements to quantify the impact of airspace restrictions due to conflict zones on CO2 emissions. Among current restrictions, we show that the Russian ban of its airspace to Western airlines following the invasion of Ukraine has the largest impact. Our analysis reveals an initial reduction of flights to and from East Asia that would have crossed the Russian territory. Routes then gradually reopened by making a detour, which led to an average increase in fuel consumption of 13% on the affected routes, with a greater impact for flights to and from Europe (14.8%) compared to flights to and from North America (9.8%). Although these flights represent only a small fraction of the daily flights, the large detours have increased global aviation CO2 emissions by 1% in 2023, equivalent to a quarter of the yet-to-be-achieved efficiency gain potential from improved air traffic management.